ChemInform Abstract: Silver Vanadium Diphosphate Ag2VP2O8: Electrochemistry and Characterization of Reduced Material Providing Mechanistic Insights. Issue 24 (23rd May 2013) - Takeuchi, Esther S.; Lee, Chia‐Ying; Cheng, Po‐Jen; Menard, Melissa C.; Marschilok, Amy C.; Takeuchi, Kenneth J.
Abstract Ag2VP2O8 is prepared by a previously reported method and its structure is confirmed by Rietveld refined powder XRD data (space group P21/c, Z = 4).